2021
DOI: 10.3389/fnins.2021.716887
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits and Attention-Deficit Hyperactivity Disorder Symptoms Associated With Greater Pain Interference and Depression, and Reduced Health-Related Quality of Life in Children With Chronic Pain

Abstract: Previous research indicates elevated levels of clinically significant traits and symptoms of autism spectrum disorder and attention-deficit hyperactivity disorder (ADHD) in children with chronic pain, but associations with functioning and depression are yet unclear. The current study examined the relationships of autistic traits and ADHD symptoms with pain interference, depression, and health-related quality of life, as well as the mediating roles of insomnia and psychological inflexibility, in children with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 100 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Second, the small sample size in the current study could be influenced the amount of the correlations. Third, various studies have shown that psychological flexibility correlates significantly with psychological health problems ranging from r = 0.2 to r = 0.8 [47,48]. This may be due to differences in different clinical populations.…”
Section: Discussionmentioning
confidence: 97%
“…Second, the small sample size in the current study could be influenced the amount of the correlations. Third, various studies have shown that psychological flexibility correlates significantly with psychological health problems ranging from r = 0.2 to r = 0.8 [47,48]. This may be due to differences in different clinical populations.…”
Section: Discussionmentioning
confidence: 97%
“…Further illuminating our findings, it is noteworthy that only 1 of 64 studies was considered weak, reflecting confidence in our synthesis and conclusions drawn. Bhandari et al 6 Birnie et al 7 Chan et al 13 Dutta et al 15 Feinstein et al 23 Feinstein et al 22 Gamwell et al 27 Kersch et al 41 Morris et al 51 Ross et al 59 Salamon et al 60 S ánchez-Rodríguez et al 61 Soltani et al 64 Stone et al 68 Stone et al 69 Yoon et al Cunningham et al 14 Evans et al 20 Hainsworth et al 32 Jagpal et al 37 Salamon et al 60 Stoner et al 67 Tran et al Pain Interference Index (PII) Balter et al 3 Holmstr öm et al 36 Lipsker et al 45 Wicksell et al 80 Wicksell et al 81 Zetterqvist et al…”
Section: Psychometric Relevancementioning
confidence: 99%
“…Psychological Factors Additionally, as implicated in a range of other psychiatric disorders including PTSD and BPD as mentioned above, emotional dysregulation has also been highlighted as a shared aspect in ADHD and fibromyalgia [289]. Executive function deficits are key features of ADHD [290][291][292] and may also affect attentional processes and so the extent to which positive coping strategies can be used for chronic pain, increasing risk of symptoms both feeling worse and having a greater negative impact on daily functioning [293].…”
Section: Attention-deficit Hyperactivity Disordermentioning
confidence: 99%
“…Having neurodevelopmental disorder ASD and/or ADHD traits in addition to chronic pain makes both quality of life and pain interference worse, in comparison with cases of chronic pain only [293]. In addition, children with chronic pain, particularly girls, may be more at risk of having a comorbid neurodevelopmental disorder go undiagnosed [129] – this relationship between chronic pain and missed diagnoses was also seen across genders in adults [370].…”
Section: Section 2: Potential Causes For and Mechanisms Of Overlap Wi...mentioning
confidence: 99%